The AI Imperative: Solving the Healthcare Workforce Crisis Through Digital Transformation - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The global healthcare system is facing a critical juncture. A confluence of factors—an aging population, increasing chronic disease burden, and a rapidly ret...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care